Estudio de prefactibilidad para la instalación de una planta productora de hojas de papel reciclado para impresión - Aquino Zarate, Hoshiwn Lorena (2020)
The main objective of this study is to evaluate the commercial, technical, financial, economic and social viability of the installation of a plant to produce recycled paper for the national market. In chapter I, the research plan is detailed, with the main objectives, hypotheses, scope of the thesis and the technical, social and economic justification. In chapter II, the market study is carried out, which determined that the demand for the project for the year 2021 would be 242 800 boxes of finished product aimed at medium and large companies in Metropolitan Lima. On the other hand, in Chapter III, it was determined that it would be more feasible to locate the plant in Lurín, Lima, mainly by the availability of raw material. Likewise, in Chapter IV, the plant size was established, which for the project is the market with 271 935 paper boxes and the breakeven point, which would be 78 829 units per year. Subsequently, in chapter V, the installed capacity was analyzed, finding that the first stage of thickening is the bottleneck. The production program for the 5-year useful life of the project was also established, with a production batch of 1 050 boxes of recycled paper. Regarding the layout of the plant, a total minimum area of 1 873 m2 was determined. Afterward, in Chapter VI, the structure and directive of the company was defined. In Chapter VII, the economic and financial aspects were evaluated, determining that the total investment required is 23'651,884.26 soles. Likewise, given that the values of the VANE = 882 082,32 soles and VANF = 3 525 099,85 soles are positive and the values of the EIRR = 21,00% and the IRR = 28,52 % are higher than the opportunity cost (COK = 19,53%), it is concluded that the project is profitable. Finally, in chapter VIII, the social evaluation was carried out, from which a favorable Product - Capital ratio of 2,12 is obtained.